Regional integration and migration in Africa : lessons from south ern and west Africa - Gumede, Vusi; Oloruntoba, Samuel O. (Samuel Ojo), 1970-; Kamga, Serges Djoyou (Serges Alain Djoyou) (Boston ; Brill : CODESRIA, 2020)
"This comparative book debates migration and regional integration in the two regional economic blocs, namely the Southern African Developme nt Community (SADC) and the Economic Community of West African States ( ECOWAS). The book takes a historical and nuanced citizenship approach t o integration by analysing regional integration from the perspective of non-state actors and how they negotiate various structures and institu tions in their pursuit for life and livelihood in a contemporary contex t marked by mobility and economic fragmentation."--
Introduction and Background -- Conceptual Underpinnings and Contempo rary Debates -- Historical and Theoretical Issues -- Migration Policies in Africa -- Migration and Regional Integration: West Africa and South ern Africa -- SADC and ECOWAS: Comparative Perspectives -- Resilient Ec onomy, Migration and Regional Integration.
Includes bibliographical references (p. 179-191) and index.
Keywords: Regionalism -- Africa, Southern; Regionalism -- Africa, West; Africa, Southern -- Emigration and immigration; Africa, West -- Emigration and Immigration; Africa, Southern -- Economic integration; Africa, West -- Economic integration